Study on Nucleation and Growth Mechanism of Iron Crystal Grain in Coal-based Shaft Furnace Direct Reduction Iron Pellets by Microwave Heating - Zhu-Cheng Huang; Zhen-yuan Liao; Bing Hu; Ling-yun Yi; Yuan-bo Zhang (The Minerals, Metals and Materials Society, 2011)
"Nucleation and growth mechanism of iron crystal grain in coal-based shaft furnace direct reduction process by microwave heating were investigated by optical microscope, scanning electron microscope and EDX. The results indicate that microwave has selectivity on various minerals which absorb microwaves. The high temperature in certain area of pellets and thermal stress on the interface of minerals are formed, results in the wustite grain smashed along the joints, and iron crystal grains turned out a spherical shape obviously. The iron crystal nucleus is formed firstly at the edge of wustite, on the interface between grains and in the holes in pellets, and grows gradually while reduction carries on from surface layer to inner core. Microwave heating promotes the rate of transportation and accumulation of the iron crystal grain, increases growth rate of iron crystal grain and contributes to formation of dense iron-jointed crystal texture eventually.IntroductionMicrowave energy as a new energy, which selectively heating materials through internal energy dissipation, has the advantages of heating uniformity, high thermal efficiency, fast heating, clean and pollution-free compared to conventional heating motheds. Microwave energy also has obvious superiority in increasing productivity. Thus, it has been widely used in many areas, including electronics, food processing, chemical, medicine, environmental protection, and family life etc [1]. As a rapidly developed green metallurgical method, microwave heating also has been widely recognized by areas of grinding, pretreatment, pre-reduction, drying, furnacing, metal extraction, and waste materials processing and utilization. Some research achievements are gradually putting into practice, showing great potential in chemical and metallurgical industry [2-3]."